R&D investments and employment decisions as a function of enterprise size and regional population density before and during COVID-19 - Aarstad, Jarle; Jakobsen, Stig-Erik; Kvitastein, Olav Andreas (Frontiers in Research Metrics and Analytics, 2023)
Norwegian data show that from 2018 to 2020, enterprises in densely populated regions increased R&D investments relative to those in sparsely populated regions, but not from 2016 to 2018. Therefore, COVID-19 likely induced the shift. The findings imply that densely populated regions have become more R&D-intensive, while sparsely populated regions have become less R&D-intensive during the pandemic. Small enterprises increased both R&D investments and employment from 2018 to 2020 relative to large enterprises and the analyses control for regression toward the mean effects. The findings were similar to those observed in the period from 2016 to 2018, which rules out COVID-19 as an explanation. Instead, the waves of data indicate a long-term trend where small enterprises increased R&D investments and employment.